Dynamics and driving forces of agricultural landscapes in Southern Ethiopia – a case study of the Chencha and Arbaminch areas. Issue 3 (3rd May 2016) - Assefa, Engdawork; Bork, Hans-Rudolf
Abstract : Agricultural landscapes in Ethiopia have undergone unprecedented changes. The direction of change, however, is unsustainable as manifested in land degradation, biodiversity loss, and low agricultural productivity. The objective of this study is to examine the patterns and trends of agricultural landscape development and responses of the local people within the framework of the dynamics of demography, socioeconomic conditions, politics, and natural resources in the Chencha and Arbaminch areas, Southern Ethiopia, during the last century. Information on cultivated and grazing land areas was acquired by satellite image interpretation. Interviews and group discussions provided important information on agricultural land use systems. A review and an analysis of secondary sources and documents of past studies were also used for trend analysis as a baseline and a supplement to oral history. The results show that cultivated land was expanded by 39% from 1973 until 2006, but per capita farming land holdings decreased enormously. In the same period of time, grassland shrank by 69% thus causing a significant decrease in livestock. Cultivated land scarcity can mostly be related to demographic pressure, which was exacerbated by government policy, land tenure, and the nature of subsistence agriculture. The farmers, however, were resourceful and developed skills over millennia to cope with the problems associated with population density and scarce resources. However, these traditional land use activities and land management practices have been deteriorating recently. Land use planners and environmental managers should take local knowledge and innovation into account in order to make sound decisions for the future.